Performance characteristic evaluation of a bismuth germanate-based high-sensitivity 5-ring discovery image quality positron emission tomography/computed tomography system as per National Electrical Manufacturers Association NU 2-2012 - Jha, Ashish; Mithun, Sneha; Puranik, Ameya; Purandare, Nilendu; Shah, Sneha; Agrawal, Archi; Rangarajan, Venkatesh (World Journal of Nuclear Medicine, 2019)
National Electrical Manufacturers Association (NEMA) provides guidelines to assess the performance of Positron Emission Tomography (PET). A PET/CT scanner, Discovery IQ, GE Medical systems, Milwaukee, USA was installed in our department which has high a sensitivity PET component. We have performed the NEMA NU-2 2012 quality control tests to evaluate this system on site before clinical use. Performance measurements of the PET scanner were made using the NEMA NU2-2012 procedures for spatial resolution, scatter fraction, sensitivity, count rate loss and random coincidence estimation, Noise Equivalent Count Rate (NECR) and image quality. As per NU2 2012, spatial resolution was measured at 1 cm, 10 cm and 20 cm vertically from the centre and at each of these points resolution was measured at tangential, radial and axial directions. Sensitivity was measured at centre and 10 cm off center vertically from the center. The system sensitivity is reported as an average of the two measured values. Scatter fraction and NECR measurements, Image quality test was also performed. The tangential, radial and axial FWHM were 4.99 mm, 4.20 mm and 4.79 mm at 1 cm off centre, 5.49 mm, 4.69 mm and 4.81 mm at 10 cm off centre and 7.99 mm, 5.07 mm and 4.95 mm at 20 cm off centre respectively. The absolute sensitivity of this scanner was found to be 20.1 cps/kBq. The scatter fraction calculated from the decay method was 37.94% and NECR was 125 kcps. The peak NECR was achieved at activity concentration of 8.7 KBq/ml and the count loss below the peak NECR was found to be 0.68%. Image quality test for, contrast recovery, background variability and lung error residual mean met all specifications. Overall PET performance of Discovery IQ whole-body scanner was satisfactory and the scanner met all the performance specifications required by NEMA 2012.
Keywords: Discovery image quality; image quality; National Electrical Manufacturers Association evaluation; National Electrical Manufacturers Association NU-2 2012; Q. clear; VPHD